Acute variations in retinal vascular oxygen content in a rabbit model of retinal venous occlusion. - Gilberto Raul Lopez Jaime (Public Library of Science (PLoS), 2012)
Purpose To study the variation in intravascular oxygen saturation (oximetry) during an acute retinal vein occlusion (RVO) using hyperspectral computed tomographic spectroscopy based oximetry measurements. Methods Thirty rabbits were dilated and anesthetized for experiments. Baseline oximetry measurements were made using a custom-made hyperspectral computed tomographic imaging spectrometer coupled to a fundus camera. RVO were induced using argon green laser following an intravenous injection of Rose Bengal. RVO induction was confirmed by fluorescein angiography. Retinal oximetry measurements were repeated in arterial and venous branches one hour after RVO induction and up to 4 weeks afterwards. Comparison of retinal oximetry before and after vein occlusion was made using the Student T-test. Results One hour after RVO induction, we observed statistically significant reductions in the intravascular oxygen saturation in temporal retinal arteries (85.1 ± 6.1% vs. 80.6 ± 6.6%; p<0.0001) and veins (71.4 ± 5.5% vs. 64.0 ± 4.7%; p<0.0001). This decrease was reversible in animals that spontaneously recannulated the vein occlusion. There were no statistically significant differences in oxygen saturation in the nasal control arteries and veins before and after temporal vein RVO induction. Conclusions We demonstrate, for the first time, acute changes in the intravascular oxygen content of retinal vessels 1 hour after RVO. These changes are reversible upon spontaneous recannulation of retinal vessels. This study demonstrates that hyperspectral computer tomographic spectroscopy based oximetry can detect physiological variations in intravascular retinal oxygen saturation. The study also provides the first qualitative and quantitative evidence of the variation in retinal vascular oxygen content directly attributable to an acute retinal vein occlusion.